Prise en compte de l’occupant dans une démarche interdisciplinaire de réhabilitation durable - Maxime Quentin; Éric Henry; Patrizia Laudati (Développement Durable et Territoires)
An interdisciplinary approach based human and social sciences can lead to a better understanding of the householder concerning the process of rehabilitation. The one described here insists on the informative and communicative analysis established between the user and his environment. Users' satisfaction is at the core of the procedure. It includes the user’s perception of comfort without trying to change his behaviour. The aim is to offer different scenarios of rehabilitation that include at the same time the measurement of comfort and the measurement perceived by the householder. To illustrate this point, we have chosen to work on the thermal comfort example.